Coupling matrix synthesis and design of a chained-function waveguide filter - Lim, Y.P. (2019)
This paper presents, for the first time, the coupling matrix synthesis for the application of a chained-function to waveguide filters. The realization of this filter is carried out by successively adding one resonator at a time by comparing the simulated responses of each stage with those obtained using the coupling matrix synthesized from the chained-function. A sixth-order chained-function waveguide bandpass filter centered at 28 GHz with a fractional bandwidth of 2 is demonstrated. The simulated S-parameter responses and the sensitivity analysis pertaining to the manufacturing errors is included. The chained-function waveguide has the lowest percentage changes in terms of the return loss performance given the same amount of distortion as compared with those of the Chebyshev response filters. This results in a lower sensitivity rate with respect to the manufacturing errors, leading to achieving a high-performance filter implementation with a minimum tuning effort. Â© 2018 IEICE